Pediatric bronchogenic cysts in the head and neck region: A study of 10 surgical cases and a review of the literature - Wei Chen; MengRou Xu; Qingyu Wang; Hongming Xu; Jiarui Chen; Xiaoyan Li (Frontiers Media S.A., 2022)
ObjectiveTo explore the clinical characteristics and surgical treatment of children with bronchogenic cysts (BCs) in the head and neck region.MethodsA retrospective study of 10 pediatric patients with BCs in the head and neck region treated in Shanghai Children's Hospital during 2011 to 2022 was performed.ResultsBased on their pathological diagnosis, 10 patients with BCs in the head and neck were identified. The most common location was the neck (8 patients, 80%; 2 midline neck, 6 lateral neck), followed by the ventral tip of tongue (1 patient), and the posterior pharyngeal wall (1 patient). Misdiagnosed as lymphangioma in 5 cases, cyst in 3 cases, thyroglossal duct cyst (TGDC) in 2 cases and congenital pyriform sinus fistula (CPSF) in 1 case preoperative. The median follow-up period after surgery was 4.68 (range, 0.67-9.25) years. All 10 patients underwent complete resection without recurrence or other complications.ConclusionsAlthough extremely rare, BCs should be considered in the differential diagnosis of midline and lateral neck masses or intraoral cysts in children. Surgical excision is recommended in BCs, and the diagnosis is definitively confirmed by histopathology.